Climate-smart farmer Peris Owiti's has a demonstration plot for women - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmer Peris Onyango Owiti is receiving seeds and trainings on various hybrid crops by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) East Africa program and partners. The idea was to create a demonstration plot for women in her area with Peris as their teacher. Here they would learn more about drought- and pest resistant, fast-maturing hybrid crops while seeing with their own eyes what new farming practices could offer them and their families. Peris has been doing this work since February of this year. Hear her story and how she is making a contribution to her community and fellow women. Learn more on our web site: www.ccafs.cgiar.org